State history. Native Americans. Litigation. 1929-04-04 (1929)
Montana tribes press big claim through Sanders. - Everett Sanders, secretary to the administration during the Coolidge administration, will lead the fight of the Assinniboine Indians of Montana to recover $17,000,000 they claim from the federal government.